Kidney temperature course during living organ procurement and transplantation. (23rd December 2016) - Kuipers, Thomas G. J.; Hellegering, Joyce; El Moumni, Mostafa; Krikke, Christina; Haveman, Jan Willem; Berger, Stefan P.; Leuvenink, Henri G.; Pol, Robert A.
Summary: Little is known about the actual kidney graft temperature during the 2nd warm ischemia time (WIT2). We aimed to determine the actual temperature course of the WIT2, with emphasis on the 15 °C metabolic threshold. Data of 152 consecutive adult living donor kidney transplantations were collected. The mean WIT2 was 41.3 ± 10.1 (SD) minutes with a temperature of 5.4 °C at baseline which gradually increased to 13.7, 17.4, and 20.2 °C after 10, 20, and 30 min, respectively. The percentage of kidneys with a temperature of 15 °C or higher was 81.2% after 20 min and 97.5% after 30 min. Duration of surgery (95% CI: −0.017 to −0.002, P = 0.02), multiple veins (95% CI: 0.0003–2.720, P = 0.05) and WIT2 (95% CI: 0.016–0.099, P = 0.006) were associated with a rapid temperature increase. No correlation could be determined between a rapid temperature rise and diminished graft function. This study showed a rapid increase in kidney temperature during WIT2, wherein the 15 °C threshold was reached within 20 min in more than 80% of the patients.